Integration of Islamic-based anti-corruption education in Al Qur’an and hadith study courses - Smeer, Zeid B; Mubasyiroh, Mubasyiroh; Hamim, Hamim; Rosyidah, Inayatur (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Anti-corruption education from an Islamic perspective for students is an alternative in eradicating Corruption. integration education anti-Corruption in the Qur'an and Hadith courses is education anti-Corruption merges in Al-Qur'an and Hadith courses through development Theory because of course part the material contain payload score and behavior anti-Corruption, as well as through development learning methods and media. Based on data processing obtained for category moral knowing It was found that the ICP PAI students of UIN Maliki Malang class of 2020 reached 82%. For category moral feeling by 86%, and for category moral action as much as 84%. Then the students of ICP PAI UIN Maliki Malang batch of 2020 are more put forward heart conscience and empathy for anti-corruption actions with percentage which enough tall that is as big as 86%. In other words, the integration of anti-corruption education from an Islamic perspective in Al-Qur'an and Hadith courses contribute positively to the internalization of anti-corruption educational values in students